A Proposed Architectural Framework of Orthogonal Handshaking Authentication Protocol (OHSAP) for Secure Private Cloud Data Transactions on Client based Access mechanism - Sirajudeen, M.Mohamed; Siddiq, M.Abubacker (IJRDO-Journal of Applied Science, 2015)
In the emerging trends in cloud computing help to reduce the operating cost for requiredresources irrespective of the geographical barriers. Simultaneously, the data/information access byvarious clients arises too many security issues in the existing cloud deployment models. Especially,profitable oriented transactions give more attention for secure data transmission between the clientsand cloud service providers (CSP). Usually, the programmers /researchers follow a method ofencryption /decryption to protect the data from intruders. In this proposed approach faintly differentfrom the existing one with some additional features for the cloud service provider’s location in order tostore the encrypted data (ED) and the Encryption key. The security related protocols are usually runover the untrusted networks regarding to ensure the secure data transactions. Private Clouds play animportant role to access confidential /privacy information’s for an individuals or an organization. It willbe composed into two major issues: client based access mechanism and server based access mechanism.In this proposed architectural framework to describe the client based access mechanisms with allrequired features.